PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) IPA BERBASIS INKUIRI TERBIMBING DAN KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI PEMANASAN GLOBAL KELAS VII SMP - Fitri, Tri Rahmadhani; Darmawati, Darmawati; Febrita, Elya (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research is to produce a valid student’s worksheet based on guided inquiry and students' ability in creative minding for global warming theory for seventh grade in junior high school. This research was conducted at the Biology Education Laboratory of the Department of Mathematics and Natural Sciences Faculty of Riau University and the Special Assistance Junior High School Dumai in April-August 2019. This type of research is a research development using the ADDIE model carried out until the development stage. There are 4 students’worksheet developed. Data collection instruments in this study were students’worksheet assessment / validation sheets, and student questionnaire responses. After students’worksheet was developed, it was validated by 5 validators then a simulation was conducted on 12 4th semester students of biology education Riau University, and the trials were limited to 26 Class VII students in Dumai Special Assisted Middle School. Validation results show the mean score of the design aspects of the 5 students’worksheet developed is 3.59 very valid categories, the mean score of pedagogical aspects is 3.58 very valid categories, and the average score of aspects of content worthiness is 3.48 very valid categories. The overall score for all aspects of students’worksheet was 3.54, a very valid category. Simulation results show a mean score of 3.44 with a very good category. Limited trial results show an average score of 3.33 in the excellent category. The results of the analysis of the answers in the limited trial showed an average value of 89.5 (non-experimental) in both categories. The results of the analysis of the answers in the limited trial showed a value of 92.8 (experimental) in either category. The validation results of the students’worksheet based on inquiry in global warming theory on seventh grade were valid and very good.Key Words: Development, Students’ Worksheet, Guiding Inquiry, Ability in Creative Thinking, Global Warming